2002
DOI: 10.2320/matertrans.43.292
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Surface Hot Shortness due to Cu in Recycled Steels

Abstract: The most serious problem in the recycling of steel is the occurrence of surface hot shortness during hot deformation due to the mixing of Cu from scrap into steels. Tin accelerates the effect of Cu. The surface hot shortness is caused by liquid embrittlement, that is, formation of the liquid Cu-enriched phase through preferential oxidation of Fe atoms at the steel/scale interface during heating for hot deformation and penetration of this Cu-enriched phase into the grain boundaries. Decrease in the amount of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…The reduction in production costs has been also reported by effectively using low-quality iron ores and by omitting or shortening the dephosphorization process. Furthermore, Shibata et al [14] have found that susceptibility to surface hot shortness decreases on increasing P content up to 0.1 % in Fe-0.1 %C-0.5 %Mn-0.5 %Cu steel. In this case, the possibilities can be explored to replace or reduce judiciously the costlier element Ni with P to even more than 0.1 %.…”
Section: Introductionmentioning
confidence: 97%
“…The reduction in production costs has been also reported by effectively using low-quality iron ores and by omitting or shortening the dephosphorization process. Furthermore, Shibata et al [14] have found that susceptibility to surface hot shortness decreases on increasing P content up to 0.1 % in Fe-0.1 %C-0.5 %Mn-0.5 %Cu steel. In this case, the possibilities can be explored to replace or reduce judiciously the costlier element Ni with P to even more than 0.1 %.…”
Section: Introductionmentioning
confidence: 97%
“…However, the addition of certain elements, such as nickel, silicon, boron, carbon, and phosphorus, is reported to be effective in controlling this problem. [1][2][3][4][5][6] Furthermore, controlling the reheating conditions, such as temperature and the atmospheric water vapor concentration in the atmosphere, also contribute to resolving this problem. 7,8) Therefore, it is important to understand how Cu is distributed when steel is oxidized.…”
Section: Introductionmentioning
confidence: 99%
“…At conditions of higher or lower temperatures, the sensitivity of surface cracks is reduced. 5,8) In addition, the oxidizing atmosphere also has an impact; atmospheric water vapour increases the number of crack on the steel surface.…”
Section: Introductionmentioning
confidence: 99%